SUPERVISI KEPALA SEKOLAH MENGEMBANGKAN BAHASA RESEPTIF ANAK - Badrul Mudarris; Romiatun Hasanah (Universitas Nurul Jadid, 2021)
This study aims to analyze and examine the principal's supervision of teachers in developing children's receptive language. The researcher used a qualitative case study approach. This research was conducted at RA Perwanida III, Paiton Probolinggo. The results showed that implementing the principal's supervision of teachers in developing receptive language at RA Perwanida III was as follows; first problem mapping, second perception equalization, third implementation of supervision activities, and fourth results and follow-up plans. This research implies that supervision must be carried out in a planned and systematic manner with continuous improvement.